Isolation, Selection, and Cultivation of Antagonistic Lactic Acid Bacteria Against Postharvest Pathogenic Fungi in Grapes - Chau, Ngo Thi Tuong; Yen, Nguyen Nhu; Le, Nguyen Thi Tu; Ly, Phan Thi Thao; Thien, Le Van (VNU Journal of Science: Earth and Environmental Sciences; Vol 39 No 4DO - 10.25073/2588-1094/vnuees.4996, 2023)
I ncorporation of probiotics with edible coatings to preserve and improve the shelf life of fresh fruits has gained more popularity in the food industry. This study aimed to isolate, select lactic acid bacteria (LAB) that are antagonistic to postharvest pathogenic fungi in grapes ( Vitis vinifera L.), and determine the optimal conditions for their biomass production. Fungi were isolated from decaying grapes on Potato Dextrose Agar medium (PDA) supplemented with 1% Chloramphenicol at 25 ºC for five to seven days. LAB were isolated on MRS agar medium at 37 ºC for two to three days. Isolates with antifungal capability were selected using the overlay technique. LAB were cultured in MRS broth at pH 4-8, 25-40 ºC for two to five days. Effects of pH and temperature on the antifungal activity of cell-free supernatant (CFS) were investigated at respectively pHs of 4.5 to 6.5 and temperatures of 60, 80 and 100 ºC for 2 hours. We identified and selected the fungal strain Nn4 with high infection density (1.5×10 5 CFU/g) to be the grape postharvest pathogenic fungus of interest. For antagonistic bacteria, we selected the lactic acid bacterial strain Ln9 with the highest antifungal activity against strain Nn4 (37.9 mm in diameter). The suitable cultivation conditions for biomass production of strain Ln9 were at pH 5.0, 30 ºC for 2 days. The antifungal activity of CFS was drastically reduced when the medium pH was adjusted to 6.5 but not reduced after heat treatment. It is evidential that the antifungal properties of probiotics can be related to the production of organic acids.